2009
DOI: 10.1042/bj20081488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the phenylurea hydrolases A and B: founding members of a novel amidohydrolase subgroup

Abstract: Mycobacterium brisbanense strain JK1, a bacterium capable of degrading the herbicide diuron, was isolated from herbicide-exposed soil. A gene/enzyme system with diuron hydrolase activity was isolated from this strain and named PUH (phenylurea hydrolase) B (puhB/PuhB) because of its close similarity to the previously characterized PUH A (puhA/PuhA). Both PUHs were heterologously expressed, purified and characterized. The PUHs were found to oligomerize as hexamers in solution, with each monomer containing a mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 44 publications
1
79
1
Order By: Relevance
“…The highest similarity (48 to 50% amino acid sequence identity) was observed with phenylurea hydrolases from A. globiformis D47 and Mycobacterium brisbanense JK1 (19).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The highest similarity (48 to 50% amino acid sequence identity) was observed with phenylurea hydrolases from A. globiformis D47 and Mycobacterium brisbanense JK1 (19).…”
Section: Resultsmentioning
confidence: 83%
“…High homology (Ͼ40% of amino acid identity) was observed only with the phenylurea hydrolases PuhA and PuhB. These enzymes, which are involved in the degradation of several phenylurea herbicides such as diuron and linuron (19), were found to oligomerize as homohexamers. Analysis of proteins of subfamily cd1292 identified after a PSI BLAST search to be related to molinate hydrolase identified a set of 853 proteins to be the most closely related.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, phenylurea hydrolase-encoding genes puhA and puhB were identified in the linuron-degrading actinomycetes Arthrobacter globiformis D47 (52) and Mycobacterium brisbanense JK1 (23), respectively. PuhA and PuhB form a novel branch within the metal-dependent amidohydrolase superfamily (23). Regarding the degradation of DCA, Dejonghe (9) and Breugelmans et al (6) found indications for the involvement of a multicomponent aniline dioxygenase enzyme in DCA degradation in Variovorax sp.…”
mentioning
confidence: 99%